Pengaruh Harga dan Kualitas Produk Healthy Food Terhadap Kepuasan Pelanggan PT Mitra Gemilang Agro: The Effect of Price and Quality of Healthy Food Products on Customer Satisfaction of PT Mitra Gemilang Agro - Ayu Devina Anggraini; Lela Elvira; Maria Lapriska Dian Ela Revita (Jurnal Manajemen dan Akuntansi Cakrawarti, 2026)
This research was conducted at PT Mitra Gemilang Agro, considering that customer satisfaction is one aspect that can determine a company's success in retaining customers. Customer satisfaction can be influenced by various factors, including price and product quality. This study aims to determine the effect of price and quality of Healthy Food products on customer satisfaction at PT Mitra Gemilang Agro. The method used in this study was quantitative. The sample size for this study was 95 respondents, determined using the Slovin formula. Data collection was conducted using a questionnaire with a Likert scale, and data processing was carried out using SPSS version 25. The results showed that partially, the Price variable obtained a tvalue of 1.491 < t-table 1.986, with a significance value of 0.139 > 0.05. Therefore, Price did not significantly influence Customer Satisfaction. The Product Quality variable obtained a calculated t value of 4.532 > t table 1.986 with a significance value of 0.000 < 0.05, so Product Quality has a positive and significant effect on Customer Satisfaction. Simultaneously, Price and Product Quality obtained a calculated fvalue of 43.525> ft table 3.10 with a significance value of 0.000 < 0.05, so Price and Product Quality together have a significant effect on Customer Satisfaction.